Post-colonial statecraft in South East Asia sovereignty, state building and the Chinese in the Philippines - Wong, Pak Nung (Library of international relations (Series), 2013)
"Stretched out along the Western rim of the Pacific, historically torn between Chinese and US influence, the Philippines has been troubled by internal conflicts since its independence in 1946. After decades of communist insurgency, social unrest and the 14-year dictatorship of Ferdinand Marcos, the democracy that followed in 1986 has been beleaguered by mutiny, corruption and violence. In 'Post-Colonial Statecraft in South East Asia', an historically aware ethnography of the region and the first study of its kind, Pak Nung Wong maps out the complex interweaving power structures of the tribal rulers in the northern regions of the Philippines. Featuring interviews with a range of local actors, including state officials, the Catholic Church, the military, the Chinese business community and the inarticulate ruled majority, he provides a complete picture of Filipino political culture. By focusing on the governance techniques of three frontier strongmen of the Cagayan Valley, the book argues that the success of Filipino post-colonial statecraft hinges on the integration of the provinces into the state's mechanisms of power. This is an important study which students and scholars in International Relations, Anthropology, History and Politics will find most valuable as the strategic and geopolitical significance of the Philippines becomes increasingly apparent."--Publisher's website.